Biochemical investigations into the proteolytic activities in salivary glands of the tick, Ornithodoros savignyi - Gaspar, A.R.M. (Anabella Regina Marques) (University of Pretoria, 2013)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2006.